Pengembangan Destinasi Wisata Masjid Kapal Safinatun Najah dengan Komponen Pariwisata 3A di Kota Semarang - Dyah Palupiningtyas; Andhi Supriyadi; Heru Yulianto; Aletta Dewi Maria (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2022)
Development of tourism destination of Masjid Kapal safinatun najah with 3A tourism component in Semarang City The research was designed to understand and to explain potential and tourist attraction at Safinatun Najah Mosque based on 3A of tourism component and explanation of development efforts by the administrator, government, and community as well as knowing the benefit of Safinatun Najah Mosque development. Qualitative description research is mentioned as research that produce scientific research that use description data in the form of words written or verbally off people or behaviour which observe to a group of people or an object and group of culture (Maleong J, 1991). Developing of attraction at Safinatun Najah Mosque by optimising the empty space. Developing and maintaining of amenity by continuous care and developing of accessibility by enlargement of the street traffic sign and giving the transportation of public. This development gives an economic impact such also gives a social and cultural impact.